Shifting of Governance and Justice: A Reference of Nepal - Bhattarai, Lokindra Hari (Molung Educational Frontier, 2020)
Governance is the exercise of the political, economic, social, and administrative authority to manage the nation’s affairs. Power and justice strengthen systems to support human rights, peace, unity, democracy in the country. The governance system in Nepal since the ancient period of Kirats, Lichhavis, Mallaslaid in Hindu Religion, Ved, Mundhum, Shmritis, Manab Nyayasastra, and order of the Kings. At the beginning of the modern period, after the unification of modern Nepal from Shahs, Ranas, Panchayat till the youngest republican democratic state, justice and governance make the Nepalese authority more accountable, transparent, inclusive, efficient, and participative. From the ancient to the modern times, governance emphasizes interactions between state, and social actors and among people representative themselves. Shift from Dharmasastra to judiciary and other ADR procedures since the ancient to the modern period are/ were the primary methods to govern the state. The paper aims at presenting several dimensions to analyze paradigm shift of governance and justice system from ancient period till dates where the journey from Dharmasastra to the rule of law, independent judiciary, and people’s supremacy. It highlights justice delivery in Nepal, which has slowly and gradually integrated into a centrally administered national judicial system.